2021
DOI: 10.7150/jca.60748
|View full text |Cite
|
Sign up to set email alerts
|

SNHG9 promotes Hepatoblastoma Tumorigenesis via miR-23a-5p/Wnt3a Axis

Abstract: Background: Hepatoblastoma is a common hepatic tumor occurring in children between 0-5 years. Accumulating studies have shown lncRNA's potential role in distinct cancer progression and development, including hepatoblastoma. SnoRNA host gene 9 (SNHG9) is associated with the progression of distinct human cancers, but, its specific molecular mechanisms in hepatoblastoma is not unknown. Methods: In this study, we estimated SNHG9 expression in hepatoblastoma tissue and cell lines by quantitative Real-Time Polymeras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…In lung cancer, SNHG9 played a role in cisplatin resistance by promoting the CAPRIN1 gene [ 46 ], and the knockdown of SNHG9 decreased cell proliferation and invasion [ 47 ]. With regard to liver cancers, it was shown that SNHG9 promoted hepatoblastoma tumorigenesis via miR-23a-5p / Wnt3a axis [ 48 ]. Moreover, decreasing SNHG9 reduced methylation of the GSTP1 gene and inhibited liver cancer cell proliferation, migration and invasion [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…In lung cancer, SNHG9 played a role in cisplatin resistance by promoting the CAPRIN1 gene [ 46 ], and the knockdown of SNHG9 decreased cell proliferation and invasion [ 47 ]. With regard to liver cancers, it was shown that SNHG9 promoted hepatoblastoma tumorigenesis via miR-23a-5p / Wnt3a axis [ 48 ]. Moreover, decreasing SNHG9 reduced methylation of the GSTP1 gene and inhibited liver cancer cell proliferation, migration and invasion [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prior evidence has suggested that miR-23a-5p exhibits oncogenic activity in bladder cancer (Li et al 2018) and renal cell carcinoma (Quan et al 2017), and it can additionally influence tumorigenesis and disease progression through interactions with specific lncRNAs or mRNAs. In glioblastoma, for example, the lncRNATPT1-AS1 can promote growth activity through the sequestration of miR-23a-5p (Gao et al 2021), whereas the lncRNA FLVCR1-AS1 can enhance cervical cancer cell malignancy via the miR-23a-5p/SLC7A11 axis (Zhou et al 2022) and hepatoblastoma progression is at least partially driven by the SNHG9/miR-23a-5p/Wnt3a signaling pathway (Feng et al 2021). Besides affecting tumor progression, miR-23a-5p could modulate the innate host defense by promoting mycobacteria survival and inhibiting the activation of autophagy against Mycobacterium tuberculosis (M.tb.)…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that SNHG9 exerts its biological effects by binding directly to miRNAs. For instance, SNHG9 promotes carcinogenesis in hepatoblastoma by downregulating miR-23a-5p and upregulating Wnt3a ( Feng et al, 2021 ). SNHG9, when increased in glioblastoma stem cells (GSCs), functions as a ceRNA for miR-326 and promotes the development of GSCs ( Wang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%